2014
DOI: 10.1186/1477-7827-12-34
|View full text |Cite
|
Sign up to set email alerts
|

Obesity is associated with increased seminal insulin and leptin alongside reduced fertility parameters in a controlled male cohort

Abstract: BackgroundObesity appears to be associated with male reproductive dysfunction and infertility, although this has been inconsistent and inconclusive. Insulin and leptin are known mediators and modulators of the hypothalamus-pituitary-testes axis, contributing to the regulation of male reproductive potential and overall wellbeing. These hormones are also present in semen influencing sperm functions. Although abdominal obesity is closely associated with insulin resistance (hyperinsulinaemia), hyperleptinaemia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 44 publications
6
76
1
2
Order By: Relevance
“…While a statistically significant negative relationship was detected between BMI and semen volume, concentration and motility in a comprehensive cohort study including 10665 patients conducted by Belloc et al, no relationship with morphology was detected (18). In another study with 42 patients conducted by Leisegang et al, it was reported that BMI level and sperm concentration are negatively correlated and no correlation was detected with motility and morphology (19). In a cohort study, which Stewart et al conducted with 225 fertile male patients, it was reported that BMI and sperm count are negatively correlated (20).…”
Section: Discussionmentioning
confidence: 90%
“…While a statistically significant negative relationship was detected between BMI and semen volume, concentration and motility in a comprehensive cohort study including 10665 patients conducted by Belloc et al, no relationship with morphology was detected (18). In another study with 42 patients conducted by Leisegang et al, it was reported that BMI level and sperm concentration are negatively correlated and no correlation was detected with motility and morphology (19). In a cohort study, which Stewart et al conducted with 225 fertile male patients, it was reported that BMI and sperm count are negatively correlated (20).…”
Section: Discussionmentioning
confidence: 90%
“…A small study with 42 men further reported that obese men had decreased sperm concentration and vitality, as well as increased sperm DNA fragmentation. Additionally, seminal and serum leptin concentrations were correlated in those individuals, suggesting that leptin may have a deleterious effect on male reproductive function through an direct action on HPT axis or on specific sites (Leisegang et al 2014). Indeed, the presence of Ob-R in testis, and particularly in testicular cells such as Leydig and Sertoli cells, also suggests that leptin may have a direct action on testicular cells (Fig.…”
Section: Energy Balance Hormonal Dysfunction and Male Reproductionmentioning
confidence: 92%
“…Male obesity and (MS) are associated with hypogonadism [27]. Insulin and leptin, which are important regulators of male reproduction via modulation of the hypothalamus-pituitary-testes (HPT) axis, were detected in the seminal fluid of obese infertile men [28]. One such adipose-derived hormone is leptin, which is best known as a regulator of food intake and energy expenditure via hypothalamic-mediated effects.…”
Section: Discussionmentioning
confidence: 99%